System log clustering approaches for cyber security applications: A survey. Issue 92 (May 2020) - Landauer, Max; Skopik, Florian; Wurzenberger, Markus; Rauber, Andreas
Abstract: Log files give insight into the state of a computer system and enable the detection of anomalous events relevant to cyber security. However, automatically analyzing log data is difficult since it contains massive amounts of unstructured and diverse messages collected from heterogeneous sources. Therefore, several approaches that condense or summarize log data by means of clustering techniques have been proposed. Picking the right approach for a particular application domain is, however, non-trivial, since algorithms are designed towards specific objectives and requirements. This paper therefore surveys existing approaches. It thereby groups approaches by their clustering techniques, reviews their applicability and limitations, discusses trends and identifies gaps. The survey reveals that approaches usually pursue one or more of four major objectives: overview and filtering, parsing and signature extraction, static outlier detection, and sequences and dynamic anomaly detection. Finally, this paper also outlines a concept and tool that support the selection of appropriate approaches based on user-defined requirements.